Relationship between Sedentary Time and physical activity in patients with Non-Alcoholic Fatty Liver Disease (Journal of Fatima Jinnah Medical University, 2023)
One of the most prevalent chronic liver diseases is nonalcoholic fatty liver disease (NAFLD). Public health is currently threatened by physical inactivity and the resulting health problems. The aim of this study was to investigate the relationship between sedentary behavior and physical activity level in NAFLD patients.Methods: A cross-sectional study was carried at Allama Iqbal Medical College/Jinnah Hospital, Lahore. Purposive sampling was used to enroll 210 participants in the study. NAFLD patients aged between 18 and 80 years attending OPD were recruited after taking their informed consent. Data were entered into SPSS version 25.0 for analysis. Quantitative variables were reported as frequencies and percentages. Spearman rank correlation test was used to determine the relationship between sedentary time and physical activity level. Statistical significance was defined as a P value of 0.05 or less.Results: Total 210 patients were enrolled in current study. Majority 147(70.0) of the patients were 20-50 years old, male 126(60.0%), married 186(88.6%). The most common sign and symptoms of non-alcoholic fatty liver disease were abdominal pain 169(80.5%), followed by change in weight 130(61.9%) and constipation 125(59.5%). Majority of the patients have low and moderate physical activities and have sedentary life style. Their sitting time is almost 6 to 10 hours a day. The current study results showed a negative strong correlation between sedentary time and physical activity of patients [r = -0.650**, P-value
Keywords: NAFLD; Physical activity; sedentary life style